Siliceous zeolite-derived topology of amorphous silica - Hirokazu Masai; Shinji Kohara; Toru Wakihara; Yuki Shibazaki; Yohei Onodera; Atsunobu Masuno; Sohei Sukenaga; Koji Ohara; Yuki Sakai; Julien Haines; Claire Levelut; Philippe Hébert; et al. (Communications Chemistry)
Abstract The topology of amorphous materials can be affected by mechanical forces during compression or milling, which can induce material densification. Here, we show that densified amorphous silica (SiO2) fabricated by cold compression of siliceous zeolite (SZ) is permanently densified, unlike densified glassy SiO2 (GS) fabricated by cold compression although the X-ray diffraction data and density of the former are identical to those of the latter. Moreover, the topology of the densified amorphous SiO2 fabricated from SZ retains that of crystalline SZ, whereas the densified GS relaxes to pristine GS after thermal annealing. These results indicate that it is possible to design new functional amorphous materials by tuning the topology of the initial zeolitic crystalline phases.